2012
DOI: 10.1039/c2ra21387g
|View full text |Cite
|
Sign up to set email alerts
|

Redox additive aqueous polymer gel electrolyte for an electric double layer capacitor

Abstract: A hydroquinone mediated PVA-H 2 SO 4 gel electrolyte (PHHQ) and activated carbon from bio-waste were prepared for supercapacitor fabrication. PHHQ delivered a higher capacitance (941 F g 21 at 1 mA cm 22 ) and energy density (20 Wh kg 21 at 0.33 W g 21 ) than the PVA-H 2 SO 4 gel electrolyte (425 F g 21 at 1 mA cm 22 , 9 Wh kg 21 at 0.33 W g 21 ).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
87
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(92 citation statements)
references
References 21 publications
5
87
0
Order By: Relevance
“…An innovative approach to supercapacitors has recently been developed by the introduction of a single redox additive such as hydroquione [23][24][25], methylene blue [26],p-phenylenediamin [27,28], m-phenylenediamine [29], indigo carmine [30], KI [31][32][33], Na 2 MO 4 [34] or VOSO 4 [35] into the liquid electrolyte or GPE. The specific capacitance and energy density of the supercapacitor are greatly increased as a result of the additional pseudocapacitance deriving from the electron transfer redox reaction of the redox additive.…”
Section: Introductionmentioning
confidence: 99%
“…An innovative approach to supercapacitors has recently been developed by the introduction of a single redox additive such as hydroquione [23][24][25], methylene blue [26],p-phenylenediamin [27,28], m-phenylenediamine [29], indigo carmine [30], KI [31][32][33], Na 2 MO 4 [34] or VOSO 4 [35] into the liquid electrolyte or GPE. The specific capacitance and energy density of the supercapacitor are greatly increased as a result of the additional pseudocapacitance deriving from the electron transfer redox reaction of the redox additive.…”
Section: Introductionmentioning
confidence: 99%
“…[81] In this case, the capacitances are not only contributed by electrode materials but also contributed from the electrolytes. To date, various redox-active mediators contain organic molecules like hydroquinone (HQ), [82,83] methylene blue (MB), [84] indigo carmine, [85] p-phenylenediamine (PPD), [86] m-phenylenediamine, [87] lignosulfonates, [88] and ionic redox active species like KI, [89,90] VOSO 4 , [91] Na 2 MO 4 , [92] and CuCl 2 [93] have been extensively studied. The GPEs containing redoxactive mediators have been extensively explored in carbonbased supercapacitors, pseudocapacitors, and Li-O 2 battery.…”
Section: Redox-active Gpesmentioning
confidence: 99%
“…Roldan et al 14 reported an increase in capacitance from 320 to 901 F g À 1 by adding hydroquinone to H 2 SO 4 electrolytes. Similarly, Senthilkumar et al 15 used hydroquinone addition into polyvinyl-alcohol H 2 SO 4 gel electrolyte to increase the capacitance from 425 to 941 F g À 1 , and they reported potassium iodide addition into aqueous H 2 SO 4 electrolyte 16 to increase the capacitance from 472 to 912 F g À 1 . These increases in capacitances were attributed to rapid faradaic reactions at the electrode/electrolyte interface that occurred by introducing mediators (hydroquinone/quinine, iodide/iodine pairs) into electrolytes, which augmented the pseudocapacitive contribution to the system.…”
mentioning
confidence: 99%